Stentless Root Replacement versus Tissue Valves in Infective Endocarditis - A Propensity-Score Matched Study - Easo,Jerry (2020)
Abstract Introduction: People with aortic/prosthetic valve endocarditis are a high-risk cohort of patients who present a challenge for all medically involved disciplines and who can be treated by various surgical techniques. Methods: We analyzed the results of treatment of root endocarditis with Medtronic Freestyle® in full-root technique over 19 years (1999-2018) and compared them against treatment with other tissue valves. Comparison was made with propensity score matching, using the nearest neighbor method. Various tests were performed as suited for adequate analyses. Results: Fifty-four patients in the Medtronic Freestyle group (FS group) were matched against 54 complex root endocarditis patients treated with other tissue valves (Tissue group). Hospital mortality was 9/54 (16.7%) in the FS group vs. 14/54 (25.6%) in the Tissue group (P=0.24). Cox regression performed for early results demonstrated coronary heart disease (P=0.004, odds ratio 2.3), among others, influencing early mortality. Recurrent infection was low (1.8% for FS and Tissue patients) and freedom from reoperation was 97.2% at a total of 367 patient-years of follow-up (median of 2.7 years). Conclusion: The stentless xenograft is a viable alternative for treatment of valve/root/prosthetic endocarditis, demonstrating a low rate of reinfection. The design of the bioroot allows for complex reconstructive procedures at the outflow tract and the annular level with at an acceptable operative risk. Endocarditis patients can be treated excluding infective tissue from the bloodstream, possibly with benefits, concerning bacteremia and recurrent infection. Furthermore, the use of the stentless bioroot offers varying treatment options in case of future valve degeneration.